2022
DOI: 10.1001/jamaoncol.2022.1047
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of the mTOR Inhibitor, Vistusertib, Combined With Anastrozole in Patients With Hormone Receptor−Positive Recurrent or Metastatic Endometrial Cancer

Abstract: IMPORTANCEEndometrial cancer is often hormone-dependent and treated with aromatase inhibitors. The PI3K-AKT-mTOR pathway deregulation observed in endometrial cancer drives hormonal resistance, thus supporting the rationale of combining mTOR inhibitor with endocrine therapy. OBJECTIVE To evaluate the safety and efficacy of vistusertib in combination with anastrozole in the treatment of women with hormone receptor−positive recurrent or metastatic endometrial cancer. DESIGN, SETTINGS, AND PARTICIPANTSThe VICTORIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Akt inhibitor has been used in treating ER/PR-positive breast cancer to disrupt the function of the PI3K/Akt/mTOR pathway and alleviate endocrine resistance [ 16 , 32 ]. The mTOR inhibitor has also been tested as an EC therapy in phase II clinical trials [ 33 , 34 ]. We previously found that activating the mTOR-4EBP1/eIF4G pathway could promote proliferation and inhibit apoptosis in RL95-2 and HEC-1A EC cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Akt inhibitor has been used in treating ER/PR-positive breast cancer to disrupt the function of the PI3K/Akt/mTOR pathway and alleviate endocrine resistance [ 16 , 32 ]. The mTOR inhibitor has also been tested as an EC therapy in phase II clinical trials [ 33 , 34 ]. We previously found that activating the mTOR-4EBP1/eIF4G pathway could promote proliferation and inhibit apoptosis in RL95-2 and HEC-1A EC cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“… 328 Currently, no mTOR kinase inhibitors are approved, but some are under evaluation, such as AZD2014, sapanisertib, and vistusertib. 367 , 368 , 369 Notably, vistusertib plus anastrozole improved was superior to anastrozole alone in HR‐positive, recurrent or metastatic endometrial cancer in the form of PFS and ORR with manageable adverse events. 369 Dual inhibition of PI3K and mTOR is a direction, and many dual PI3K/mTOR inhibitors are in their early‐stage trials, such as gedatolisib, paxalisib, samotolisib, voxtalisib, and apitolisib.…”
Section: Selective Small Molecule Kinase Inhibitorsmentioning
confidence: 99%
“… 367 , 368 , 369 Notably, vistusertib plus anastrozole improved was superior to anastrozole alone in HR‐positive, recurrent or metastatic endometrial cancer in the form of PFS and ORR with manageable adverse events. 369 Dual inhibition of PI3K and mTOR is a direction, and many dual PI3K/mTOR inhibitors are in their early‐stage trials, such as gedatolisib, paxalisib, samotolisib, voxtalisib, and apitolisib. 370 For example, samotolisib is a promising dual PI3K/mTOR inhibitor and had a clinical benefit on PFS in metastatic castration‐resistant prostate cancer with tolerable side effects when combined with enzalutamide.…”
Section: Selective Small Molecule Kinase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In HR+ metastatic endometrial patients, although endocrine therapy allows response in 15–30% of cases, it is only of short duration. In order to avoid resistance to endocrine therapy, we recently evaluated safety and efficacy of combining the aromatase inhibitor Anastrozole with the mTOR inhibitor Vistusertib, in 73 patients with advanced or relapsed HR+ endometrial cancer maximally treated with one line of chemotherapy [ 4 ]. This multicentric, randomized open‐label phase I/II VICTORIA trial (NCT02730923) showed that Vistusertib and Anastrozole combination treatment (V + A, n = 49) improve neoplastic control compared to Anastrozole alone (A, n = 24), with a progression‐free rate at 8 weeks of 67% in the V + A arm and of 39% in the A arm.…”
Section: Introductionmentioning
confidence: 99%